Memetakan Perubahan Organisasi Dalam Desain Learning Organization Pada Usaha Kecil Menengah di Kota Malang - Sugeng Mulyono; Enlik Kresnaini (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This research aims at analyzing the implementation of learning organization at small and medium enterprises (SMEs); the effects of learning organization on individuals’ ability; the effects of individuals’ ability on SMEs changes; and the effects of learning organization on changes of SMEs. The population of this research is all SMEs located in Malang and the samples are 298 SMEs taken through multi stages sampling. The primary data were collected using a questionare and interviews, whereas the secondary were obtain from relevant documents. The collected data were analyzed using descriptive and structural equational modelling (SEM). The results show that learning organization has a significant positive effect on individuals’ ability; the individuals’ ability has a significant positive effect on changes of SMEs; and learning organization has a significant positive effect on changes of SMEs, as indicated by C.R > 2 and value of P < 0,05.